Effective usage of seashell waste to improve the strength characteristics of silty sand. (2022) - Muthu Lakshmi, S.; Geetha, S.; Selvakumar, M.; Mahalakshmi, S.; Pavithra, A.
Abstract: Proper disposal of Seashell (SS) waste is one of the major issues faced by the fishery industry all over the world. Millions of tons of SS waste are being dumped in marine waters and also along the coastal areas leading to environmental degradation. SS waste takes long period to decompose thus leading to wastage of land areas which otherwise could have been utilized for other useful purposes. To overcome this global issue of dealing with SS waste, an effort has been made in this research work to utilize SS waste as an additive with locally available Silty Sand (SM) subgrade soil to improve their strength characteristics. SS waste was added to soil in two different forms, in crushed form of size 4.75 mm to 75 µm and in uncrushed form of size 10 mm to 4.75 mm, by varying the percentage of SS waste from 10% to 40% by dry weight of soil. Soaked and unsoaked California Bearing Ratio (CBR) tests were conducted, to optimize the quantity of SS waste to be added to SM soil for which maximum CBR strength was attained. From the results, it was observed that maximum soaked and unsoaked CBR of 6% and 9.9% respectively was attained for SM with 25% uncrushed SS. Corresponding, percentage decrease in flexible pavement thickness of about 49% and 38.5% was calculated, based on the soaked and unsoaked CBR values respectively. Similary, maximum soaked and unsoaked CBR of 6.9% and 12.9% respectively was observed for SM with 35% crushed SS. Corresponding percentage decrease in flexible pavement thickness of about 52.8% and 48.2% was calculated, based on soaked and unsoaked CBR values respectively. Thus, it can be concluded that utilization of SS waste with soil, lead to a sustainable and economical construction.